Antioxidant activity of Maytenus ilicifolia root bark - Vellosa, JCR; Khalil, N. M.; Formenton, VAF; Ximenes, V. F.; Fonseca, L. M.; Furlan, Maysa [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Oliveira, OMMF (Elsevier B.V., 2006)
Maytenus ilicifolia is an important plant with potential on cancer treatment and has been largely used in Brazil and other countries. We have evaluated the crude ethanolic extract of M. ilicifolia as a potential antioxidant source using an assay based on the bleaching of the radical monocation 2,2'-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS(center dot+)) and by HOCl scavenger capacity. Trolox and uric acid were used as positive controls. The results indicated M. ilicifolia root bark as a great source of antioxidants based on its potential as scavenger of radicals. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Maytenus ilicifolia; antioxidant activity